Dinâmica do carbono e nitrogênio em argissolos com plantação de Eucalyptus sp. - Wink, Charlote (2013)
Understanding the dynamics of carbon and nitrogen associated with the physical and chemical properties of the soil are important for conscious planning the use and management of land under cultivation of eucalyptus in order to act positively on the quality of the environment. The aim of this study was to evaluate the dynamics of carbon and nitrogen in surface and depth in soils cultivated with Eucalyptus sp., of different ages, in Central Depression and Southeast, Rio Grande do Sul. For this, was evaluated: a) a) through nonparametric and multivariate analyzes, the ratio of total organic carbon and total nitrogen with the physical and chemical properties at the surface and at depth in soils cultivated with Eucalyptus sp., replacing the native grassland; b) the accuracy of the employment Century 4.5 model in simulating the content of total organic carbon and total nitrogen in the 0.0-0.2 m layer of soils cultivated with Eucalyptus sp.; c) the distribution of total organic carbon and of total nitrogen in depth through the negative exponential mathematical model in soils cultivated with Eucalyptus sp. The dynamics of total organic carbon and total nitrogen in Eucalyptus plantations, replacing native grass, is related to the physical and chemical properties, and the use and soil management, recognized by the test nonparametric univariate and multivariate analysis. In surface soil that relationship is expressed by the variables already required at start of the simulation model of the dynamics of soil organic matter (Century Model 4.5). Depth in the profile, this association is more expressive with other properties, such as phosphorus, potassium, pHwater, calcium, magnesium, as well as fine sand, the SMP index and macroporosity. One can also consider, in the background, the coarse sand and clay. In a way this is important in the qualitative assessment of soil, since it makes inferences about the degradation process and the productivity of these soils. The native grassland had the highest similarities in the variations of soil properties in the surface layers, unlike Eucalyptus plantations in that homogeneity is more pronounced in the deeper layers of the profile. The Century Model 4.5 showed a good fit in the simulation of the stock of total organic carbon in the soil and can be used in the simulation of organic matter dynamics in native grassland and Eucalyptus plantations in the different districts. For the stocks of soil total nitrogen, even with the changes of parameters, the Century Model 4.5 could not simulate with acceptable statistical accuracy when compared to the observed data. The content of total organic carbon and total nitrogen in the soil depth of native grassland and Eucalyptus plantations has negative exponential distribution, indicating that the model was able to represent rated this dynamic. However, it should evaluate the quality of the method employed in estimating the rate of decay of these contents, since differences were estimated in the content of total organic carbon and nitrogen along the entire soil profile. Therefore, we suggest the development of new long-term experiments in Eucalyptus plantations of different ages in different soil depths in order to infer the temporal behavior of carbon and nitrogen in soil, based on the processes of migration, degradation, stability and fractions of these elements.